Changing perceptions and altered reality : emerging economies in the 1990s - Burki, Shahid Javed (World Bank WashingtonUS, 2000)
Gives the author's view of the Latin America region in 1994 and how his perceptions changed over time. Focuses on poverty and various aspects of globalization. Presents four case studies dealing with countries in crises.